Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Komitmen Organisasi Karyawan - Siti Salma Nur Izati; Munawaroh Munawaroh (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
An organization is a setting where individuals can unite and work together to accomplish shared goals, vision, and mission. A company's human resources (HR) play a major role in its success, and having talented employees can offer the organization a competitive edge. The ability of both individuals and groups to collaborate, communicate, and maintain discipline has a significant impact on an organization's effectiveness. Extracurricular activities by employees, such supporting colleagues and upholding work ethics, also help the company reach its objectives. To inspire and guide subordinates to collaborate in the face of difficulties, effective leadership is required. Ability, motivation, and interest all affect employee performance, which is also impacted by company culture, which reflects common standards and values. Employee performance and business success can both be enhanced by a positive corporate culture.